Njunjungi Tradition of Piher Rice in Lau Solu Village Marding-Ding District Karo Regency Local Wisdom Study - Nurcahayati Br Ginting; Herlina Ginting (Journal of Language Development and Linguistics, 2023)
This study aims to describe the stages of the Njujungi Beras Piher tradition, the values contained in the Njujungi Beras Piher Tradition. The theory used in this study is the theory of local wisdom expressed by Sibarani (2014). The method used in this research is a qualitative method. Based on the results of the research and the results of the analysis, the authors can conclude that the results obtained in this study are: (1) The stages of implementing the Njujungi Beras Piher Tradition, (2) The ingredients contained in the Njujungi Beras Piher Tradition, (3) The value of local wisdom that in the Njujungi Beras Piher Tradition, namely social solidarity, politeness, harmony, conflict resolution, commitment, gender management, mutual cooperation, hard work, discipline, self-control, education, welfare, preservation, cultural creativity, and gratitude.